Insights into CO2 fixation pathway of Clostridium autoethanogenumby targeted mutagenesis - Liew, Fungmin; Henstra, Anne M.; Winzer, Klaus; Kopke, Michael; Simpson, Sean D.; Minton, Nigel P. (American Society for Microbiology, 2016)
The future sustainable production of chemicals and fuels from nonpetrochemical resources and reduction of greenhouse gas emissions are two of the greatest societal challenges. Gas fermentation, which utilizes the ability of acetogenic bacteria such as Clostridium autoethanogenum to grow and convert CO2 and CO into low-carbon fuels and chemicals, could potentially provide solutions to both. Acetogens fix these single-carbon gases via the Wood-Ljungdahl pathway. Two enzyme activities are predicted to be essential to the pathway: carbon monoxide dehydrogenase (CODH), which catalyzes the reversible oxidation of CO to CO2, and acetyl coenzyme A (acetyl-CoA) synthase (ACS), which combines with CODH to form a CODH/ACS complex for acetyl-CoA fixation. Despite their pivotal role in carbon fixation, their functions have not been confirmed in vivo. By genetically manipulating all three CODH isogenes (acsA, cooS1, and cooS2) of C. autoethanogenum, we highlighted the functional redundancies of CODH by demonstrating that cooS1 and cooS2 are dispensable for autotrophy. Unexpectedly, the cooS1 inactivation strain showed a significantly reduced lag phase and a higher growth rate than the wild type on H2 and CO2. During heterotrophic growth on fructose, the acsA inactivation strain exhibited 61% reduced biomass and the abolishment of acetate production (a hallmark of acetogens), in favor of ethanol, lactate, and 2,3-butanediol production. A translational readthrough event was discovered in the uniquely truncated (compared to those of other acetogens) C. autoethanogenum acsA gene. Insights gained from studying the function of CODH enhance the overall understanding of autotrophy and can be used for optimization of biotechnological production of ethanol and other commodities via gas fermentation.